2018
DOI: 10.1021/acsami.7b17017
|View full text |Cite
|
Sign up to set email alerts
|

Nanobrass CuZn Nanoparticles as Foliar Spray Nonphytotoxic Fungicides

Abstract: Inorganic nanoparticles (NPs) have been proposed as alternative fertilizers to suppress plant disease and increase crop yield. However, phytotoxicity of NPs remains a key factor for their massive employment in agricultural applications. In order to investigate new effective, nonphytotoxic, and inexpensive fungicides, in the present study CuZn bimetallic nanoparticles (BNPs) have been synthesized as antifungals, while assessment of photosystem II (PSII) efficiency by chlorophyll fluorescence imaging analysis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 68 publications
3
98
0
1
Order By: Relevance
“…There are few studies on the absorption, transport and accumulation of nanomaterials in plants compared to the phytotoxicity of nanomaterials (Chichiriccò and Poma 2015). Nanomaterials may be absorbed by plants through root or leaf exposure, which may enhance the interaction between the plants and nanomaterials (Antonoglou et al 2018). The NPs must penetrate the cell wall and the plasma membrane before entering the plant cell.…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the absorption, transport and accumulation of nanomaterials in plants compared to the phytotoxicity of nanomaterials (Chichiriccò and Poma 2015). Nanomaterials may be absorbed by plants through root or leaf exposure, which may enhance the interaction between the plants and nanomaterials (Antonoglou et al 2018). The NPs must penetrate the cell wall and the plasma membrane before entering the plant cell.…”
Section: Discussionmentioning
confidence: 99%
“…A series of inorganic and organic nanomaterials have been developed and proven to exhibit prominent antibacterial, antifungal, and antiviral properties on phytopathogenic microbes in vitro, and some of them still exerted their toxicity effects under greenhouse and field conditions. To date, TiO 2 , CuO (Hao et al, 2017(Hao et al, , 2019Liu et al, 2017), Zn, ZnO (Xue et al, 2014;Antonoglou et al, 2018;Sun et al, 2018), carbon nanomaterials (Chen et al, 2014(Chen et al, , 2016b, Al, and Si nanoparticles (Park H.J. et al, 2006;Shenashen et al, 2017) have been reported to display toxicity toward phytopathogenic bacteria and fungi, decreasing the disease incidence.…”
Section: Introductionmentioning
confidence: 99%
“…12 Most importantly, CuZn bimetallic nanoparticles (BNPs) displayed no phytotoxic effects on tomato plants, as shown by assessing the photosystem II (PSII) efficiency of plants aer 3 h of exposure to BNPs that exhibited antifungal activity against Saccharomyces cerevisiae. 13 As a result, we can infer that CuONPs have the potential to be used as an alternative tool to combat pathogenic microbes and exhibit the notable properties of low effective concentrations and low toxicity.…”
Section: Introductionmentioning
confidence: 99%